Eleventh European Powder Diffraction Conference. Warsaw, September 19-22, 2008 (Zeitschrift für Kristallographie / Supplemente, 2009)
Zeitschrift für Kristallographie. Supplement Volume 30 presents the complete Proceedings of all contributions to the XI European Powder Diffraction Conference in Warsaw 2008: Method Development and Application,Instrumental, Software Development, Materials. Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.